Selection of stable reference genes for RT-qPCR in Rhodococcus opacus PD630 - Drew M. DeLorenzo (Nature Portfolio, 2018)
Abstract Rhodococcus opacus PD630 is a gram-positive bacterium with promising attributes for the conversion of lignin into valuable fuels and chemicals. To develop an organism as a cellular factory, it is necessary to have a deep understanding of its metabolism and any heterologous pathways being expressed. For the purpose of quantifying gene transcription, reverse transcription quantitative PCR (RT-qPCR) is the gold standard due to its sensitivity and reproducibility. However, RT-qPCR requires the use of reference genes whose expression is stable across distinct growth or treatment conditions to normalize the results. Unfortunately, no in-depth analysis of stable reference genes has been conducted in Rhodococcus, inhibiting the utilization of RT-qPCR in R. opacus. In this work, ten candidate reference genes, chosen based on previously collected RNA sequencing data or literature, were examined under four distinct growth conditions using three mathematical programs (BestKeeper, Normfinder, and geNorm). Based on this analysis, the minimum number of reference genes required was found to be two, and two separate pairs of references genes were identified as optimal normalization factors for when ribosomal RNA is either present or depleted. This work represents the first validation of reference genes for Rhodococcus, providing a valuable starting point for future research.